Pharmacovigilance of cutaneous adverse drug reactions among patients attending dermatology department at a Tertiary Care Hospital - Shweta Sharma; Dhanya Jayakumar; Dhanya S Palappalli (Wolters Kluwer Medknow Publications, 2019)
Context: Cutaneous adverse drug reactions (CADRs) are the most frequent of all manifestations of drug sensitivity that present with varied and diverse morphology and therefore, awareness about them is essential for diagnosis and prevention. Aims: To evaluate the clinical spectrum, morphology, causality, severity and preventability of cutaneous adverse drug reactions in a tertiary care hospital. Setting and Design: Descriptive study for six months in the Dermatology Department of a tertiary care hospital in Kerala. Methods and Materials: All patients of any gender and age who presented with visible skin lesions and were diagnosed or suspected cases of cutaneous adverse drug reactions were included in the study. All the relevant information was recorded using pre-structured proforma and ADR reporting form. Statistical Analysis: Data were analyzed using descriptive statistics. The quantitative variables were expressed as mean ± standard deviation and qualitative variables as frequencies and percentages. Odds ratio (OR) was calculated to assess the risk factors for severe cutaneous adverse drug reactions using SPSS 16. Results: Total 124 cutaneous adverse drug reactions were reported with mean age 39.22 ± 20.47 years, male:female ratio being 1:1.4. Most common cutaneous adverse drug reaction was maculopapular rash. Antibiotics accounted for maximum cases, of which beta-lactams were the most common. About 55.6% cutaneous adverse drug reactions occurred within 24 hours of drug administration. Mean hospital stay duration was 4.89 ± 6.23 days. Most reactions were either mild or moderate. Risk analysis revealed that concomitant use of more than one drug, delayed onset, oral route, more generalized area of involvement and medications prescribed for CNS indications were risk factors for severe cutaneous adverse drug reactions. All reactions were preventable. Majority got fully recovered. No fatality was observed. Conclusion: Identification and reporting of cutaneous adverse drug reactions reduces their future occurrences and encourages rational prescribing. The study emphasizes on having a deeper understanding of risk factors for serious cutaneous adverse drug reactions that may contribute significantly in improving their outcomes.